CARROT JUICE FOR POST PARTUM MOTHER: AN INTRODUCTION TO VEGETABLE CONSUMPTION - Gusti Ayu Tirtawati; Fonnie Kuhu; Stevany Gaby Makarau (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
The amount of breast milk is likely to affect the success of breastfeeding. Therefore, a study concerning the method to increase the milk volume is always encouraged, one of which is a method using carrot juice as the intervention to introduce the consumption of vegetables among nursing mothers. This was a qualitative study using a phenomenological approach. The four respondents that did not like vegetables and had little production of breast milk were found when the preliminary survey was conducted and they agreed to be involved as respondent by giving some answers questioned. The results showed that they did not like to consume vegetables because they did not use to consume them since young. Despite the fact that they knew the benefits of vegetables to health, they said that they did not know vegetables were good for the production of breast milk. However, they could consume the carrot juice as the initiation of vegetable consumption.